Updated Red List of bryophytes of Slovenia - Martinčič, Andrej (Hacquetia, 2016)
Based on floristic data and applied taxonomy there are currently 813 species and subspecies in Slovenia – 638 mosses, 173 liverworts and 2 hornworts. Based on the IUCN 3.1 criteria, which we applied to bryophytes following Hallingbäck et al. (1998), there are 164 species (20.17%) listed under threatened categories, of which 121 (18.97%) are mosses and 43 (24.57%) are liverworts; 7 of them (0.86%) are in the CR category, 83 (10.21%) in the EN category and 74 (9.10%) are listed under the VU category. There are 23 species (2.83%) in the near threatened (NT) category, while 163 species (20.05%) are data deficient (DD). The Least Concern (LC) category currently comprises 463 (56.95%) species.